Peningkatan Literasi Keuangan: Pendidikan Perencanaan Keuangan Personal di Kalangan Komunitas Guru SMK “Musyawarah Guru Mata Pelajaran (MGMP)” Kabupaten Malang - Muhammad Fuad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Financial literacy has been proven to have a positive effect on increasing economic welfare. Apart from that, financial literacy is also needed to mitigate the risk of crime or fraud which often occurs in the world of financial investment. Considering the importance of financial literacy, service activities through the personal financial planning education program are held to create people who are aware of the importance of financial planning. The activity was held for the community of vocational school teachers in Malang Regency (MGMP Malang). The results of the activity showed good enthusiasm from the participants. Participants felt they had gained new knowledge in the world of finance and planning. Changes in behavior and views about finances were also visible from what participants said after the training program